Comparison of Tax Avoidance Between Non-Financial Sectors at IDX (Case Study: IDX-IC Classification Period 2018-2022) - Hanifah, Nahlia; Ridwansyah, Eksa; Damayanti, Damayanti (Basecamp Economics PubMed, 2024)
Each sector has different regulations regarding tax calculation and of course there are variations in tax avoidance between these regulations. The aim of this research is to analyze the differences and comparative levels of tax avoidance practices between non-financial sectors on the Indonesian Stock Exchange with the IDX-IC classification measured by BTD, Cash ETR, Curremt ETR, GAAP ETR, LRC ETR, and TAXPLAN. The method used in this research is quantitative description. The results of the analysis show that there are differences in tax avoidance practices carried out by each sector. The findings of this research also show that, compared to other industries studied using the BTD proxy, the property and real estate industry has the lowest tax avoidance, while the research results tested with Cash ETR, Current ETR, GAAP ETR, LRC ETR, and TAXPLAN showed different results where the Property and Real Estate Sector carried out greater tax avoidance practices in the five year research period.